Correlation Analysis of Mental Workload on Academic Performance of Boarding Students During Biology Learning - Dwi Juni Artaningthias; Karunia Galih Permadani; Ferisa Prasetyaning Utami (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2025)
This study examines the correlation between mental workload and academic performance of boarding students at Ihsanul Fikri Islamic Boarding High School Mungkid during biology learning. Mental workload was measured using the Mental Effort Rating Scale, while academic performance was measured using the Students' Academic Performance Scale. Employing quantitative correlation design, the study involved 49 randomly selected twelfth-grade science students. Results revealed a strong negative correlation between mental workload on students' academic performance (- 0.647). Students’ mental workload was categorized as moderate with indicators of work performance and mental work effort has an average of “considerable effort” (98.16 and 91.43). Academic performance was also in the moderate category (92.63). These findings highlight the importance of managing academic demands through effective learning strategies and a supportive school environment to reduce mental workload and optimize students’ academic performance, especially in boarding school.